Can Good Corporate Governance Moderates The Influence of Internal Control and Integrity towards Fraud Prevention? - Maulani, Syifa Nurul; Amalia, Putri Syifa; Birton, M. Nur A. (Universitas Muhammadiyah Sidoarjo, 2024)
General Background: The prevalence of fraud in financial institutions, notably within Islamic banking, poses significant challenges due to the unique regulatory and ethical frameworks these institutions operate under. Specific Background: Despite Islamic banks employing distinct mechanisms, such as the three lines of defence for fraud prevention, incidents still occur, underscoring the necessity for effective internal controls and auditor integrity​​. Knowledge Gap: Current literature predominantly examines conventional banks, leaving a gap in understanding the factors influencing fraud prevention in Islamic banks, particularly the role of Good Corporate Governance (GCG) as a moderating factor​​. Aims: This study aims to empirically assess how internal controls and auditor integrity impact fraud prevention in Islamic banks and evaluate the moderating effect of GCG​​. Results: The study finds that internal control significantly enhances fraud prevention, while auditor integrity, though positively related, does not significantly affect fraud prevention. Moreover, GCG does not significantly moderate the relationship between internal controls or auditor integrity and fraud prevention​​. Novelty: This research contributes to agency theory by exploring the dynamics of agency relationships in Islamic banking and offers insights into the complex interplay between internal controls, auditor integrity, and governance structures​​. Implications: The findings highlight the critical need for robust internal control mechanisms and emphasize the importance of auditor integrity in fraud prevention efforts. They also suggest that relying solely on GCG may not optimize fraud prevention, indicating a need for comprehensive strategies involving all organizational levels​​.